Usability of the virtual health care in the quarantine period from May to July 2020 due to COVID-19 at the National Institute of Child Health in Peru - Wilcamango-Ríos, Dreysi (2022)
Introduction: The COVID-19 pandemic caused face-to-face outpatient care in health establishments to be restricted, the government establishes actions to continue providing said health services. Objective of the study: To describe the usability of the virtual health care in the COVID-19 quarantine period at the National Institute of Child Health (INSN) of Peru. Material and methods: Cross-sectional study. 7,697 patients were admitted to the INSN for virtual outpatient consultation from May to July 2020. The sampling was simple random and there was a sample of 374 participants who met the selection criteria. The telehealth usability questionnaire (TUQ) was used. Parents of patients who received virtual consultation were interviewed by telephone. Results: The average age of the interviewees was 36.2 years, mostly women and from Lima. The average age of the patients treated is 6.7 years, being mostly male (51.3%). The Smartphone was the most used device (97.6%); medical services the most consulted (84.4%), most recurrent pathologies related to the respiratory system (10.4%). 55.2% and 57.4% of the participants totally agree on the usefulness and ease of use of virtual medical care, respectively. Conclusions: The use of telehealth in the INSN had a positive impact, it managed to connect patients with their doctor in order to continue with their treatments and provide an optimal medical care response in real time.